Kedudukan Batal dan Kebatalan Akta Notaris/PPAT (Studi Kasus Putusan MA No. 666 PK/PDT/2011) - Kunardi Kunardi (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2017)
Cancellation and inaccuracy in the description of civil case ruling MA No. 666PK / Pdt / 2011, are two different things but used for the same reasons. Related to the cancellation of land and building purchase agreement of land and building by notarial deed, not by PPAT deed, which occurred on February 13, 1990 as follows: first, the agreement was made within 6 months before the death of Indrawati Dharmaputera which was accompanied by her husband is the covert effort to get rid of the bezit rights, and, secondly, the effort for the defendant to master the budel with the title of sale and purchase and heirs. Thus, the deed of sale and purchase and the power of attorney are valid and retroactive in its application. The cancellation of the notarial deed is in accordance with the principle of probation action causa, due to the deed of inheritance which is a rebuttal of the notarial deed which is not fulfillment of the objective element in terms of achievement, because the certificate is a joint treasure between Indrawati Dharmaputera and Krishna Dharmaputera which has civil rights, can be submitted reverse.